Lead-free low-melting-point glass as bonding agent for TiO2 nanoparticles. Issue 5 (1st March 2021) - Lopez-Esteban, S.; Cabal, B.; Borrell, A.; Bartolomé, J.F.; Fernandez, A.; Faraldos, M.; Bahamonde, A.; Moya, J.S.; Pecharroman, C.
Abstract: This work is a study of the properties of TiO2 -anatase nanoparticles attached by a low-melting point inorganic glass (530°C). Unlike other low-melting glasses, this composition does not contain any toxic metal. Likewise, it shows an excellent wettability on ceramic nanoparticles. A small addition of 5 vol% of glass remarkably enhances the mechanical strength of the composites with respect to pure TiO2 calcined at the same temperature, becoming twice this value. Self-cleaning properties analyzed using the methylene blue 385 nm UV-A photodegradation test showed that, after different UV-light periods, the photo-efficiency of TiO2 -anatase was not altered by the presence of this glass.